Penentuan Varietas Padi Unggul yang Akan Ditanam Berdasarkan Potensi Hasil Menggunakan Metode Analytic Hierarchy Process-Weighted Product (AHP-WP) - Tunggul Prastyo Sriatmoko; Nurul Hidayat; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The increasing population in Indonesia every year, which results in increased demand for food in Indonesia. While the increase in production of the country's agricultural production is still lacking, resulting in the government doing imports to meet food needs. Therefore, an effort is needed to improve better production, especially in rice, which is the staple food of the Indonesian population, one way to increase production is by planting seeds of superior varieties of rice. However, many criteria need to be considered in choosing which rice varieties are suitable to choose from in making choices. From these problems, there are several methods that can be implemented in solving problems with a system that is able to provide advice on the type of rice planted using the Analytic Hierarchy Process (AHP) method to give weights and the Weighted Product (WP) method is used to calculate alternative ranks and take values the highest as a final recommendation. In the testing phase with an accuracy method comparing the results of recommendations from the system compared to recommendations from experts, the resulting accuracy rate is 90.19607843%, so that it can be concluded that the AHP and WP methods can be used in recommending superior types of rice because they have high accuracy values above 90% nearing perfect from expert data.